Contract Law in Online Lending Practice - Ayu Kholifah; Arini Rufaida (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This study aims to identify the law of agreement on the practice of online lending that is developing in Indonesia. This research is a normative research with a contract law approach. Methods Data collection is done by the library method (literature). The results show that online lending practices are developing in Indonesia, applications that operate as online loan facilities include legal, illegal applications, and applications labeled as Financial Services Authority or OJK in Indonesia, Ministry of Communication and Information of the Republic of Indonesia, and Indonesian Joint Funding Fintech Association or AFPI in Indonesia. Online loan transactions that require borrowing to obtain funds, the application operator only verifies personal identity as a condition of the agreement. Therefore, the legal concept of agreement in online lending practices is that it does not meet the provisions of the agreement system and contains rights and obligations between parties and the disclosure of public information on online lending, so that online lending practices are exclusive and have defects in all online lending practices.